An Analysis of Chinese Foreign Policy Based on its Relations with Countries that Support Taiwan : Case Studies of USA, Czech Republic and the Vatican - Štráberger, Jiří; Garlick, Jeremy; Veselá, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The issue of Taiwan is a key consideration in Chinese foreign policy and bears significant influence on the foundation of China's international relations - the One China Principle. This thesis analyses bilateral relations between China and three countries that act in violation of the One Chin Principle. The purpose of this analysis is to see how China reacts to various forms of violation of this principle and how it shapes int foreign policy. The method used is a comparative case study based on constructivist theory.
Vedoucí práce: Jeremy Alan Garlick
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses